Quantifying center of pressure variability in chondrodystrophoid dogs. (August 2017) - Blau, S.R.; Davis, L.M.; Gorney, A.M.; Dohse, C.S.; Williams, K.D.; Lim, J-H.; Pfitzner, W.G.; Laber, E.; Sawicki, G.S.; Olby, N.J.
Highlights: The mean center of pressure (COP) in chondrodystrophoid dogs sits ∼8 cm caudal to the interscapular region on midline. COP moves from side to side once per step cycle and rostral and caudal twice per step cycle in walking dogs. COP variability from the mean while walking is low, is not affected by limb length but is affected by walking speed. COP variability of healthy dogs lends a basis for comparison for future research of dogs with spinal cord injuries. Abstract: The center of pressure (COP) position reflects a combination of proprioceptive, motor and mechanical function. As such, it can be used to quantify and characterize neurologic dysfunction. The aim of this study was to describe and quantify the movement of COP and its variability in healthy chondrodystrophoid dogs while walking to provide a baseline for comparison to dogs with spinal cord injury due to acute intervertebral disc herniations. Fifteen healthy adult chondrodystrophoid dogs were walked on an instrumented treadmill that recorded the location of each dog's COP as it walked. Center of pressure (COP) was referenced from an anatomical marker on the dogs' back. The root mean squared (RMS) values of changes in COP location in the sagittal (y) and horizontal (x) directions were calculated to determine the range of COP variability. Three dogs would not walk on the treadmill. One dog was too small to collect interpretable data. From the remaining 11 dogs, 206 trials were analyzed. Mean RMS for change in COPx per trial was 0.0138 (standard deviation, SD 0.0047) and for COPy was 0.0185 (SD 0.0071). Walking speed but not limb length had a significant effect on COP RMS. Repeat measurements in six dogs had high test retest consistency in the x and fair consistency in the y direction. In conclusion, COP variability can be measured consistently in dogs, and a range of COP variability for normal chondrodystrophoid dogs has been determined to provide a baseline for future studies on dogs with spinal cord injury.